2018
DOI: 10.3389/fphys.2018.00051
|View full text |Cite
|
Sign up to set email alerts
|

High Fat Diet Attenuates the Anticontractile Activity of Aortic PVAT via a Mechanism Involving AMPK and Reduced Adiponectin Secretion

Abstract: Background and aim: Perivascular adipose tissue (PVAT) positively regulates vascular function through production of factors such as adiponectin but this effect is attenuated in obesity. The enzyme AMP-activated protein kinase (AMPK) is present in PVAT and is implicated in mediating the vascular effects of adiponectin. In this study, we investigated the effect of an obesogenic high fat diet (HFD) on aortic PVAT and whether any changes involved AMPK.Methods: Wild type Sv129 (WT) and AMPKα1 knockout (KO) mice age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 54 publications
4
52
0
1
Order By: Relevance
“…The current results indicated that HF diet fed rats exhibited decreased levels of circulating adiponectin and downregulation of its gene expression. Oppositely, hyperleptinemia was detected with upregulation of its gene expression in agreement with some data presented previously (Arita et al, 1999; Trayhurn and Beattie, 2001; Almabrouk et al, 2018). Interestingly, adiponectin level is inversely but leptin is directly correlated to obesity and insulin resistance (Koleva et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…The current results indicated that HF diet fed rats exhibited decreased levels of circulating adiponectin and downregulation of its gene expression. Oppositely, hyperleptinemia was detected with upregulation of its gene expression in agreement with some data presented previously (Arita et al, 1999; Trayhurn and Beattie, 2001; Almabrouk et al, 2018). Interestingly, adiponectin level is inversely but leptin is directly correlated to obesity and insulin resistance (Koleva et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…It has been proposed that adiponectin induces anti-contractile effects through several mechanisms, including hyperpolarization of vascular smooth muscle cells, stimulating NO release and enhancing endothelial NO production (Xia & Li, 2017). Moreover, adiponectin reduces vascular oxidative stress by inhibiting NADPH oxidase (Antonopoulos et al 2015). We show that the anti-contractile activity of PVAT was absent in adult male offspring of mothers exposed to GIH, which is in keeping with other studies of a loss of anti-contractile activity in PVAT-intact mesenteric arteries from 12-and 24-week-old male rat offspring of dams a fed a high-fat diet (Zaborska et al 2016).…”
Section: Figure 10 Metabolic and Vascular Effects Of Gestational Intmentioning
confidence: 99%
“…Inflammation diminishes the anti‐contractility effects of PVAT (Nosalski & Guzik, ) and also reduces adiponectin secretion (Almabrouk et al . ) in mice. However, the effects of GIH on endothelial and PVAT function in offspring from GIH are unknown.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Increased production of reactive oxygen species, which inactivates endothelial-derived nitric oxide (NO) 16,17 , may explain reduced agonist-induced vasodilation in obese animals. Impaired endothelium-dependent vasodilation in obesity may also arise from changes in potassium channel activity [18][19][20] , NO release 20 , or how perivascular adipose tissue modulates endothelial function [21][22][23] . The number of diverse signaling mechanisms proposed to account for endothelial dysfunction in obesity demonstrates how complex changes occur in this cell layer, and point to changes in another regulator that is common to each dysfunction.…”
Section: Introductionmentioning
confidence: 99%